2020
DOI: 10.1186/s13007-020-00601-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stable reference genes for qPCR studies in common wheat (Triticum aestivum L.) seedlings under short-term drought stress

Abstract: Background: Quantitative PCR (qPCR) is one of the most common and accurate methods of gene expression analysis. However, the biggest challenge for this kind of examinations is normalization of the results, which requires the application of dependable internal controls. The selection of appropriate reference genes (RGs) is one of the most crucial points in qPCR data analysis and for correct assessment of gene expression. Because of the fact that many reports indicate that the expression profiles of typically us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…Additionally, novel candidate genes were identified which displayed a constant expression level. This aligns well with a previous study, which reported that novel reference genes identified by genome-wide in silico analysis outperformed typical reference genes in common wheat [34].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, novel candidate genes were identified which displayed a constant expression level. This aligns well with a previous study, which reported that novel reference genes identified by genome-wide in silico analysis outperformed typical reference genes in common wheat [34].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, novel candidate genes were identified which displayed a constant expression level. This aligns well with a previous study, which reported that novel reference genes identified by genome-wide in silico analysis outperformed typical reference genes in common wheat [32].…”
Section: Discussionsupporting
confidence: 92%
“…We had to screen the most suitable RGs for studying the HupA‐biosynthesis. Based on the CPM value of transcriptome sequencing and reported literatures (Chen et al, 2019 ; Dudziak et al, 2020 ; Wu et al, 2020 ), 10 traditional and three new candidate RGs were chosen (Table 1 ) . Especially for three new candidate RGs, they had stable expression in full‐length transcriptome sequencing but have not been used as RGs before.…”
Section: Discussionmentioning
confidence: 99%